(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical symptoms and early postoperative outcomes of primary hyperparathyroidism treated with parathyroidectomy at the Thoracic Surgery Department of Bach Mai Hospital during the period 2024-2025. Subjects and methods: A retrospective and prospective descriptive study was conducted on 38 eligible patients who underwent surgery at the Thoracic Surgery Department of Bach Mai Hospital from March 2024 to June 2025. Results: The female/male ratio was 2.8/1, the average age was 58.68 years, the average surgical time was 56.18 ± 13.73 minutes, 1/38 patients had parathyroid cancer, all patients showed a reduction in parathyroid hormone and blood calcium levels after surgery, there were no cases of bleeding, and no deaths. Conclusion: Minimally invasive surgical resection of parathyroid tumors for the treatment of primary hyperparathyroidism is a very safe and effective surgical method.